Keanekaragaman Jenis Tumbuhan Kantong Semar (Nepenthes spp.) di Taman Nasional Batang Gadis - Lazuardi, Lazuardi; Lestari, Rizki (CV. ITTC INDONESIA, 2025)
This research aims to determine the type, diversity index and species of Nepenthes spp. most dominates in Batang Gadis National Park. Sampling was carried out at three locations as representatives of each section in Batang Gadis National Park using mapping plots measuring 5m × 5m with 10 plots in 2 transects at each station. Each transect has 5 plots placed in a zigzag manner with a distance of 5 meters between plots. The research results showed that there were 7 types of Nepenthes spp. in Batang Gadis National Park, namely Nepenthes gymnamphora Nees, Nepethes tobaica x spectabilis, Nepenthes rhombicaulis Sh. Kurata, Nepenthes rafflesiana Jack, Nepenthes tobaica x rhombicaulis, Nepenthes naga, and Nepenthes tobaica Danser. Diversity of Nepenthes spp. in the area classified as moderate, with H' = 1.259. Station I is classified as low, with H' = 0.682, station II is classified as medium, with H' = 1.042 and station III is classified as low with an H' value of 0. Dominated by Nepenthes gymnamphora with a stable dominance index at stations I and II, and unstable at station III.